动力锥蜗杆传动的优化设计 - 熊矢 (Jixie chuandong)
To reduce the contact stress between teeth surfaces in the working transmission in the design of the power spiroid gearing, and to make the sizes and weights of the spiroid gears not be too large, an optimum design method of the multi-objects is proposed.